Analisis Unsur Instrinsik Puisi 'Kalah dan Menang' Karya Sutan Takdir Alisjahbana - Rahma, Fitriani; Wulan, Diah Nawan; Syukriady, Dwi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2025)
The analysis of intrinsic elements is the main key to comprehensively understanding the meaning of the poem “Kalah dan Menang” (Defeat and Victory). Through the study of theme, diction, rhyme, rhythm, figurative language, imagery, and moral message, the poem’s meaning can be clearly revealed, enabling readers to gain a deeper understanding and a solid basis for appreciating and analyzing literary works. This study aims to identify the moral message contained in the poem “Kalah dan Menang” by Sutan Takdir Alisjahbana. The research employs a qualitative descriptive method using a close reading technique. The data source is the text of the poem “Kalah dan Menang,” which is analyzed through interpretation of meaning, identification of themes, and examination of stylistic aspects and moral values. The results of the intrinsic analysis show that the poem portrays various human experiences in facing life’s challenges. It invites readers to view every experience, whether defeat or victory, as an opportunity to learn and grow, and emphasizes the importance of perseverance and optimism in overcoming difficulties in different life contexts. Furthermore, the poem conveys a profound moral message about balance in life. According to Sutan Takdir Alisjahbana, life is a dynamic process that requires wisdom in responding to various experiences. This poem has universal value because its message is relevant to readers from diverse life contexts.